2013
DOI: 10.1007/s13312-013-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of Language Evaluation Scale Trivandrum for children aged 0–3 years — LEST (0–3)

Abstract: LEST (0-3) is a simple, reliable and valid screening tool for use in the community to identify children between 0-3 years with delay in language development, enabling early intervention practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…With one item delay the sensitivity and specificity of LEST were 95.8% and 77.5% respectively. Positive predictive value and negative predictive value were 14.2% and 99.8% (18).…”
Section: Methodsmentioning
confidence: 93%
“…With one item delay the sensitivity and specificity of LEST were 95.8% and 77.5% respectively. Positive predictive value and negative predictive value were 14.2% and 99.8% (18).…”
Section: Methodsmentioning
confidence: 93%
“…Two item delay was considered as LEST positive in this study, which is same as suggested by MKC Nair et al, in their study. 7 The prevalence of speech and language delay is 6% in this study population. In a study at CDC, Trivandrum the prevalence was 4.5%.…”
Section: No Statistically Significant Association Was Observed Betweementioning
confidence: 68%
“…In a study at CDC, Trivandrum the prevalence was 4.5%. 7 In a similar study by Shiji et al, from Cochin, the prevalence was 5.5%. 8 The prevalence was 6.2% in a study from North India by Sidhu et al 9 Tomblin et al, found that 87% of children with articulation disorders were boys.…”
Section: No Statistically Significant Association Was Observed Betweementioning
confidence: 78%
“…Language is divided into 2 components, first the receptive language which means understanding and second the expressive language which means talking. 1 Children with any developmental abnormalities will first seek help from a pediatrician, so it would be necessary to involve a screening tool which helps in early identification of any type of developmental delay in them. Delay in language development is often an early and most sensitive indicator of intellectual disability, autism spectrum disorder or social communication disorder and specific learning disorders.…”
Section: Introductionmentioning
confidence: 99%